Estudo da interferência de diferentes dietas nutricionais sobre as ações antiinflamatória e analgésica do Etoricoxib (Arcóxia®) - Bianchetti, érica Silva (2006)
Etoricoxib is a new medicine expected to lead the next generation of selective inhibitors of COX-2 Presently the focus of many clinical assays it is a potent fast-action second generation coxib and the most selective of all The purpose of this study was to evaluate the interference of different nutritional diets in the anti-inflammatory and analgesic actions of etoricoxib and also the interactions of this NSAID plus different diets and their gastric and hematological side effects The following assays were carried out a) paw edema induced by carrageenin b) granuloma test c) dermatitis induced by croton oil d) vascular permeability in rats e) writhing test in mice f) formalin test g) gastric ulcers by stress and h) evaluation of the hematological parameters after sub-chronic treatment With regard to edema by carrageenin the etoricoxib-treated group showed a maximum peak of edema 49.04% (1.061 +- 0.1886) the other groups showed the following percentages of inhibiton etoricoxib + hyperproteic diet 30.2% (1.4537 +- 0.0955) etoricoxib + hyperlipidic diet 35.96% (64.04 +- 0.0578) etoricoxib + hyperglicidic diet 35.35% (1.346 +-0.0423) etoricoxib + standardized diet 33% (1.2968+-0.047) all of them in relation to the control group (2.0825+-0.1886) and the results were statistically significant (p < 0.01) However when the groups treated with etoricoxib associated to different diets were compared there was no statistically significant difference In the granuloma test the daily oral administration of 1 mg/kg of etoricoxib during 6 days significantly (p < 0.01) inhibited the formation of granulomatous tissue 57.02% (153.2 +- 21.908) the other groups showed the following percentages of inhibition etoricoxib + hyperlipidic diet 59% (144.98 +- 9.632) etoricoxib + hyperproteic diet 47.5% (185.575 +- 26.043) etoricoxib + hyperglicidic diet 38.5% (217.4 +- 21.318) etoricoxib + standardized diet 47.13% (166.583 2 +- 2.229) all of them in relation to the control group (353.475 +- 37.692) In the croton oil-induced dermatitis the edema of the control group had 10.33 mg The treatment with etoricoxib (1 mg/kg) associated with different nutritional diets showed inhibition of the edema but not significantly when compared to the control group The inhibition percentages were etoricoxib-treated group 7.86% (9.525 +- 1.345) etoricoxib + hyperproteic diet 31.43% (7.0875 +- 1.160) etoricoxib + hyperlipidic diet 35.6% (6.6625 +- 1.523) etoricoxib + hyperglicidic diet 39.5% (6.2571 +- 1.362) etoricoxib + standardized diet 30.7% (7.1875 +- 1.130) *p < 0.05 (Student s t test) when compared to the control group (10.3375 +- 1.462) In the vascular permeability by histamine etoricoxib (1 mg/kg) etoricoxib + hyperproteic diet etoricoxib + hyperlipidic diet etoricoxib + hyperglicidic diet and etoricoxib + standardized diet exhibited the following inhibition percentages 5.29% -31.4% -31.3% 4.05% and 15.82 respectively These results were not significant when compared to the control group (527.862 +- 66.869) In the writhing test the administration of etoricoxib (1mg/kg) inhibited the algogenic process in 9.32% (49.86 +- 4.166) When associated with different nutritional diets the inhibition percentages were hyperproteic diet 29.27% (38.9 +- 6.166) hyperlipidic diet 11.36% (48.75 +- 5.384) hyperglicidic diet 9.81% (49.6 +- 6.775) standardized diet -7.3% (59 +- 4.946) In the formalin test both in the acute and late phase all the treatments caused significant (p < 0.05) inhibitions of the hyperalgesic process etoricoxib (1mg/kg) 47.74% (62.71 +- 8.462) etoricoxib + hyperproteic diet 74.64% (30.428 +- 5.163) etoricoxib + hyperglicidic diet 68.61% (37.67 +- 5.308) etoricoxib + hyperlipidic diet 46.46% (64.25 +- 5.662) etoricoxib + standardized diet 68.2% (38.17 +- 5.528) when compared to the control group (120 +- 5.021) In the late phase the percentages of inhibition were 84.4% (10.142 +- 2.98) for etoricoxib 82.65% (11.28 +- 2.705) for etoricoxib + hyperproteic diet 66.16% (22 +- 11.781) for etoricoxib + hyperlipidic diet 98.72% (0.18 +- 0.0) for etoricoxib + hyperglicidic diet and 99.74% (0.16 +- 0.1667) for etoricoxib + standardized diet in comparison with the control group (65 +- 4.167) In the test of stress-induced ulcer the animals treated with etoricoxib (1mg/kg) + standardized diet showed the highest lesion index when compared to the other groups The lowest lesion index was shown by the group treated with etoricoxib + hyperlipidic diet whose significance was p < 0.01 (Student s t test) when compared to the control group The hematological parameters in the groups treated with etoricoxib (1mg/kg) + hyperlipidic diet (19.637 +- 3.879) and etoricoxib + hyperglicidic diet (19.3 +- 4.562) showed statistically significant differences in the hematocrit (HCT) in relation to the group treated only with etoricoxib (40.5375 +- 2.410) for p < 0.01 (Student s t test) There was a significant difference in the group treated with etoricoxib + hyperglicidic diet (8.9 +- 1.940) in relation to the group treated with etoricoxib (19.9 +- 2.134) (Student s t test) In the erythrocyte dosage the group etoricoxib + hyperglicidic diet (3.82125 +- 0.893) showed a significant difference when compared to the group treated with etoricoxib (9.4037 +- 1.027) (p < 0.01 Student s t test) No statistically significant differences were observed in the other hematological parameters The evaluation of the ponderal development of the animals treated with etoricoxib (1mg/kg) and etoricoxib assiciated with different kinds of nutritional diets showed no significant differences between the treated and control groups however the group treated with etoricoxib + hyperglicidic diet revealed lower ponderal development than the other groups With regard to diuresis there were variations in all the groups For water and feed consumption variations were practically similar in all the experimental groups The weight of the organs from different groups of animals treated with etoricoxib (1mg/kg) and etoricoxib associated with different nutritional diets showed no significant differences when compared to the control group The mean weight of the organs are within the normal parameters for rats The results suggest that a) the association of etoricoxib to different kinds of diets did not change the anti-inflammatory effect in the present assays b) the association of different types of diets potentialized the analgesic effect mainly when associated to hyperproteic diet for peripheral pain and hyperglicidic diet for central pain c) the association of etoricoxib to hyperglicidic diet decreases the gastric lesion index d) the use of etoricoxib alone did not interfere with the hematological parameters e) the association of etoricoxib to hyperglicidic diet interfered with the hemoglobin and erythrocyte index f) the treatment of the sub-chronic phase (30 days) with etoricoxib alone and etoricoxib associated to different nutritional diets caused no changes on the ponderal development diuresis and water and feed consumption